2020
DOI: 10.1103/physrevb.102.195147
|View full text |Cite
|
Sign up to set email alerts
|

NQR and NMR spectra in the odd-parity multipole material CeCoSi

Abstract: We theoretically study NQR and NMR spectra in the presence of odd-parity multipoles originating from staggered antiferromagnetic and antiferroquadrupole orderings. For the f-electron metal, CeCoSi, which is a candidate hosting odd-parity multipoles, we derive an effective hyperfine field acting on Co nucleus generated from electronic origin multipole moments at Ce ion under zero and nonzero magnetic fields. We elucidate that emergent odd-parity multipoles give rise to sublattice-dependent spectral splittings i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…For example, the zigzag [91][92][93][94][95], honeycomb [96][97][98][99], and diamond [100][101][102] structures are typical prototypes with the sublattice-dependent DM interaction. Another example is a bilayer structure system where the sign of the DM interaction is opposite for the different two layers [103][104][105][106]. Although the above lattice structures with the sublattice degree of freedom have attracted great interest owing to the findings of an antiferromagnetic (AFM) SkX [107][108][109][110][111][112] and intriguing dynamics [113][114][115][116][117][118][119], the effect of the sublattice-dependent DM interaction on the stabilization of the SkX has not been fully clarified yet [120,121].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the zigzag [91][92][93][94][95], honeycomb [96][97][98][99], and diamond [100][101][102] structures are typical prototypes with the sublattice-dependent DM interaction. Another example is a bilayer structure system where the sign of the DM interaction is opposite for the different two layers [103][104][105][106]. Although the above lattice structures with the sublattice degree of freedom have attracted great interest owing to the findings of an antiferromagnetic (AFM) SkX [107][108][109][110][111][112] and intriguing dynamics [113][114][115][116][117][118][119], the effect of the sublattice-dependent DM interaction on the stabilization of the SkX has not been fully clarified yet [120,121].…”
Section: Introductionmentioning
confidence: 99%
“…The odd parity real-space charge multipoles and associated k-space MEMs also have implications in other physical effects beyond the MCP [46][47][48][49][50]. Examples include an exotic superconducting state driven by oddparity multipole fluctuations [51,52], and the predicted Rashba effect in PTO [53], which is a direct consequence of t (k) z .…”
Section: Ir Multipole Real Spacementioning
confidence: 99%
“…4) It has been suggested that a possible origin for Phase II is an antiferroquadrupole ordering. 4,[8][9][10][11][12] Odd-parity multipole orderings originating from staggered AFM and antiferroquadrupole orderings have been proposed based on theoretical analyses. 8,9) A neutron powder diffraction study on CeCoSi shows that the magnetic moments of the two Ce atoms in the unit cell are antiferromagnetically ordered.…”
Section: Introductionmentioning
confidence: 99%